Epidemiology of epithelial ovarian cancer: a tertiary hospital based study in Goa, India - Jindal, Dweep; Sahasrabhojanee, Mrinalini; Jindal, Manjusha; D’Souza, Joachim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ovarian malignancy is seventh most common cancer in women globally. With increase in longevity, the incidence of epithelial ovarian cancer is increasing and its etiopathology remains unknown. We present preliminary epidemiological findings to help prioritize research. Methods: Present epidemiological study is retrospective, descriptive study over two years. The collected data was analyzed using SPSS software for overall survival, with respect to stage of disease and histopathology type. Multivariate analysis was done to know independent risk factors. Results: 114 cases of primary ovarian epithelial cancer were analyzed. Patients’ mean age at diagnosis was 52.1±8.96 years (median=52). 52.6% patients had stage III disease at first visit. Serous adenocarcinoma (85.05%) was the most prevalent type of histopathology followed by mucinous (7.1%), clear cell (6.1%) and Endometroid carcinoma (1.75%). Surgery followed by combination of taxane and platinum chemotherapy was first line treatment in 35%. The mean age at diagnosis was more with advancing stage (stage one 44±9.53 and stage four 55.35±9.74 years) but it was not statistically significant (p=0.098) Advancing age demonstrated poor survival (log-rank p=0.05) but survival was not significantly different in relation to histopathology (log-rank =0.629). On multivariate regression analysis age of patient (p=0.004), and stage of disease (p=0.005) were found to be independent risk factors while histopathology was not an independent risk factor (p=0.688) for survival. Conclusions: Research should be aimed to find tools for screening and early diagnosis as well as better therapeutic approaches for advanced epithelial ovarian cancer.